Professionalism of Islamic Religious Education Teachers and Their Role In Improving Student Learning Achievement at MA Darul Hikmah - Abdul Haris; Kaimudin Kaimudin; Zaenal Abidin (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to describe the professionalism of Islamic Religious Education (PAI) teachers, student achievement, the role of teacher professionalism in improving learning achievement, and the supporting and inhibiting factors at MA Darul Hikmah in Bima City. The study employed a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation and member checking. The results indicate that the professionalism of Islamic Religious Education (PAI) teachers, encompassing pedagogical, personality, social, professional, and leadership competencies, is in the good category. Student achievement also shows positive gains in cognitive, affective, and psychomotor aspects. The role of PAI teachers in improving learning achievement is realized through strengthening learning, exemplary attitudes, and fostering religious activities. Supporting factors include teaching experience, support from the principal, religious facilities, and opportunities for competency development. Inhibiting factors include limited access to training, funding, and technology-based learning media. The study concludes that the professionalism of Islamic Religious Education (PAI) teachers contributes significantly to improving student achievement, thus requiring support through competency development and the provision of adequate learning resources.